Performances of SMD Components on FR4 Substrates at Higher Frequencies - Veronica, Veronica; Umaisaroh, Umaisaroh; Alaydrus, Mudrik (Department of Electrical Engineering, 2024)
The advances of many technological wireless systems lead to development of several important microwave circuit components as supporting parts. The last century was the eye-witness of the development of many microwave components implemented on distributed, lumped elements or combination of them. In the design stage, we must fulfill the specified targets in terms of S-parameters over certain desired frequency intervals. The observation of several surface mounted devices installed in a microstrip structure is an important verification of the characteristics of the components especially at higher frequencies. We use the software ANSYS Electromagnetic Suite and AWR Design Environment as analytical tools. We verify the results by building the structures and measuring the reflection and transmission coefficient. The microstrip structure is modeled in a 1.4mm thick FR-4 substrate, with a dimension 50 mm x 50 mm is backed by a metallic copper ground with a thickness of 0.035 mm. We fabricated the structure under observation and did some measurement to verify its performances using a vector network analyzer. The computer programs give almost the same results for all cases except for the surface mounted device inductance. In this way we can rely on the computational modeling. The reflection and transmission coefficient of a 1.4mm thick microstrip line were verified by measurement with a very good similarity up to 5 GHz. The comparison of the simulated and measured reflection and transmission coefficient for resistor is almost the same for up to around 5 GHz, whereas for capacitor for up to around 6 GHz and for inductor for up to around 7 GHz.